Effects of varying curvature and width on the electronic states of GaAs quantum rings - Bruno-Alfonso, A. [UNESP]; Oliveira, T. A. de [UNESP] (Sociedade Brasileira de Física, 2006)
Stationary states of an electron in thin GaAs elliptical quantum rings are calculated within the effective-mass approximation. The width of the ring varies smoothly along the centerline, which is an ellipse. The solutions of the Schrödinger equation with Dirichlet boundary conditions are approximated by a product of longitudinal and transversal wave functions. The ground-state probability density shows peaks: (i) where the curvature is larger in a constant-with ring, and (ii) in thicker parts of a circular ring. For rings of typical dimensions, it is shown that the effects of a varying width may be stronger than those of the varying curvature. Also, a width profile which compensates the main localization effects of the varying curvature is obtained.
Keywords: Electronic states; GaAs elliptical quantum rings; Effective-mass approximation